2017
DOI: 10.1007/s00384-017-2845-1
|View full text |Cite
|
Sign up to set email alerts
|

The robotic approach significantly reduces length of stay after colectomy: a propensity score-matched analysis

Abstract: This propensity score-matched analysis suggests that RC is associated with some recovery benefits over LC. Greater experience with the technique may allow these advantages to counter some of the cost-related concerns that have deterred the more widespread utilization of robotic technology for colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…While most previous studies have shown no difference in postoperative ileus between RS and LS groups, there are exceptions that demonstrate significantly less ileus in the RS group. 19,2224 The robotic-assisted approach offers technological advantages for more complex tasks often required during sigmoidectomies for diverticular disease, such as splenic flexure takedown and dissection of a complicated phlegmon adherent to the pelvic side-wall and retroperitoneum. It is possible that performing complicated segments of the procedure with a less traumatic “minimal-touch” technique may result in decreased ileus rates, but the inconsistencies in these findings warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…While most previous studies have shown no difference in postoperative ileus between RS and LS groups, there are exceptions that demonstrate significantly less ileus in the RS group. 19,2224 The robotic-assisted approach offers technological advantages for more complex tasks often required during sigmoidectomies for diverticular disease, such as splenic flexure takedown and dissection of a complicated phlegmon adherent to the pelvic side-wall and retroperitoneum. It is possible that performing complicated segments of the procedure with a less traumatic “minimal-touch” technique may result in decreased ileus rates, but the inconsistencies in these findings warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,15 Furthermore, laparoscopic and robotic platforms have been shown to accelerate recovery comparing to traditional open approach. 23,24 We noted the period after 2012 to increase the odds of early discharge (LOS < 5). Although colorectal surgery is a known risk factor for UTI, 29 we found a continuous reduction in the complication over the included years (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…From the dataset, complications which may require reoperation such as wound infection, anastomotic leak and bleeding requiring transfusion were illustrated to be minimized for hand-assisted laparoscopic when compared to open colectomy. 24 Using the same data, robotic approach reduced postoperative systemic infection compared to laparoscopic surgery in another analysis. 23 We found minimally invasive surgery to accordingly be performed more in the most recent years (42.6% vs. 56.1%, before and after 2012 respectively).…”
Section: Discussionmentioning
confidence: 97%
“…For robotic surgery, there is an ongoing discussion on investment in equipment and costs per procedure, plus time needed for setup and docking. 64,65 The future launch of different robotic systems might lower the price to make the platform more competitive to costs of conventional laparoscopic surgery. As in all advanced surgical procedures a whole learning curriculum is required with proctoring during first cases and still with a high initial conversion rate.…”
Section: Beyond Tmementioning
confidence: 99%